Employee Performance Management: Implementation of Assessment System to Improve Organizational Effectiveness - Siswayu Gamar Maulida; Dewi Sri Yani; Editya Nurdiana (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to analyze the implementation of the employee performance appraisal system in the roof tile industry in Majalengka Regency, with a focus on identifying factors that influence the effectiveness of the performance appraisal system and its impact on employee productivity and job satisfaction. Quantitative and qualitative descriptive approaches were used in this study. A survey was conducted on 100 respondents, including employees and managers from several roof tile companies, to collect data related to job satisfaction, motivation, and productivity. In-depth interviews and focus group discussions were used to complement the survey results. Data were analyzed using statistical techniques such as correlation, regression, ANOVA, and t-test. The results showed that an unstructured performance appraisal system led to low employee satisfaction and work motivation, which ultimately had a negative impact on productivity. The correlation test showed a significant positive relationship between job satisfaction and motivation (r = 0.72, p < 0.05), while the regression test showed that an effective performance appraisal system contributed 58% to productivity (R² = 0.58). In addition, the t-test showed a significant increase in productivity after the implementation of the new system, with the average production increasing from 70 units/day to 85 units/day (t = 4.21, p < 0.05). This study recommends the implementation of a performance appraisal system based on Key Performance Indicators (KPI), training managers in providing feedback, and the use of technology to improve transparency and efficiency of evaluation.